The secreted kinase ROP18 defends Toxoplasma’s border - Fentress, Sarah J. (2011)
Toxoplasma gondii is a highly successful parasite capable of infecting virtually all warm-blooded animals by actively invading nucleated host cells and forming a modified compartment where it replicates within the cytosol. The parasite-containing vacuole provides a safe haven even in professional phagocytes such as macrophages, which normally destroy foreign microbes. In effort to eliminate the parasite, the host up-regulates a family of immunity-related p47 GTPases (IRGs), which are recruited to the parasite-containing vacuole, resulting in membrane rupture and digestion of the parasite. To avoid this fate, highly virulent strains of Toxoplasma coat the external surface of their vacuole with a secretory serine/threonine kinase, known as ROP18. At this host-pathogen interface, ROP18 phosphorylates and inactivates IRGs, thereby protecting the parasite from killing. These findings reveal a novel molecular mechanism by which the parasite disarms host innate immunity